BAKTI SOSIAL di RSUD ASEMBAGUS - Nurun Nikmah; Neny Yuli Susanti (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2022)
Social service is an activity that can increase a sense of solidarity with others, and foster a sense of sympathy to help each other, especially among the community, it is hoped that hand washing can inhibit the entry of germs into the human body through hand intermediaries, almost everyone understands the importance of hand washing. soap but did not get used to doing it right at the crucial moment. This social service activity was carried out at the Asembagus Regional General Hospital on Saturday 18 November 2017 in the Emergency Room, Laboratory, Bougenvile Room, and Orchid Room with a total of 73 participants is to create a sense of solidarity between fellow humans, increase satisfaction with health services, assist the government in disseminating healthy community movement programs, breaking the chain of disease spread and preventing the spread of endemic nosocomial viruses in hospitals. Patients and their families gain knowledge and skills in good hand washing and correct as an effort to prevent disease transmission.